Tackle characteristics associated with concussion in elite men’s rugby union: unpicking the differences between tacklers and ball-carriers - Keith A Stokes; Simon P T Kemp; Ben Jones; Sean Williams; Duncan Locke; Simon Roberts; Stephen W West; Steffan Griffin; Matt Cross (BMJ Open Sport & Exercise Medicine, 2025)
Objective To identify characteristics of tackling, of being tackled and interactions between tackle characteristics that are associated with concussion.Methods A case-control study in male professional rugby union players in England over five seasons (2016/2017 to 2020/2021) analysed characteristics of tackles that led to a clinically diagnosed concussion (cases), and a control group of tackles that did not result in a concussion. ORs were plotted against the overall frequency of each tackle characteristic.Results 231 tackles resulting in concussions (tackler 178, 77%; ball-carrier 53, 23%), alongside 9963 control tackles, were analysed. For tacklers, ‘head to torso’ (Lower CI OR Upper CI; 4.0 6.5 10.7) had relatively low odds of concussion compared with ‘no head contact’. ‘Head to knee’ had the highest odds of concussion (75.3 155.8 322.4), but ‘head to hip’ occurred more frequently and had the highest number of concussions per 1000 tackles (3.1/1000 tackles). For ball-carriers, ‘head to head’ contact had the highest odds of concussion (56.7 104.3 192.0). When ‘tackler body position’ was ‘upright’, the odds of concussion to the tackler were significantly higher when contacting the ball-carrier’s ‘head and neck’ versus their ‘torso’ (3.0 23.7 206.7).Conclusions Lower tackles reduce the chances of concussion to ball-carriers. The influence of tackle height on concussion to tacklers is more nuanced, but the chances are relatively low when contact is made with the ball-carrier’s torso. These findings support ongoing implementation of strategies to reduce concussion risk by lowering tackle height to target the torso.